1996
DOI: 10.1128/mcb.16.9.4614
|View full text |Cite
|
Sign up to set email alerts
|

Specific DNA Replication Mutations Affect Telomere Length in Saccharomyces cerevisiae

Abstract: To investigate the relationship between the DNA replication apparatus and the control of telomere length, we examined the effects of several DNA replication mutations on telomere length in Saccharomyces cerevisiae. We report that a mutation in the structural gene for the large subunit of DNA replication factor C (cdc44/rfc1) causes striking increases in telomere length. A similar effect is seen with mutations in only one other DNA replication gene: the structural gene for DNA polymerase alpha (cdc17/pol1) (M.J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 43 publications
3
103
0
Order By: Relevance
“…Introduction of dominant negative CTC1 A227V; V259M mutant into the CTC1 L1142H mutant background resulted in further telomere elongation, suggesting that CTC1 (and the CST complex) cooperates with DNA Pol‐α to negatively regulate telomerase. These findings are reminiscent of observations revealing that disrupting the interactions between CDC13 and DNA Pol‐α in yeast and CTC1 and DNA Pol‐α in mouse cells both result in telomere elongation (Adams & Holm, 1996; Chen et al., 2013; Grossi, Puglisi, Dmitriev, Lopes & Shore, 2004; Qi & Zakian, 2000). Our data also highlight the significant differences in telomere length maintenance mechanisms between normal and cancer cells.…”
Section: Discussionsupporting
confidence: 57%
“…Introduction of dominant negative CTC1 A227V; V259M mutant into the CTC1 L1142H mutant background resulted in further telomere elongation, suggesting that CTC1 (and the CST complex) cooperates with DNA Pol‐α to negatively regulate telomerase. These findings are reminiscent of observations revealing that disrupting the interactions between CDC13 and DNA Pol‐α in yeast and CTC1 and DNA Pol‐α in mouse cells both result in telomere elongation (Adams & Holm, 1996; Chen et al., 2013; Grossi, Puglisi, Dmitriev, Lopes & Shore, 2004; Qi & Zakian, 2000). Our data also highlight the significant differences in telomere length maintenance mechanisms between normal and cancer cells.…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with these data, we did not observe dramatic cell cycle delays in the asf1⌬ single-mutant cells, although the peaks were mildly broadened because of cell size heterogeneity. In contrast, rfc1-1 cells accumulated in the G2/M phase of the cell cycle, as previously reported (Adams and Holm 1996). The poorly growing asf1⌬ rfc1-1 mutant cells displayed a much more dramatic delay than the single-mutant cells, and the vast majority of cells existed in a single broad peak with approximately 2N DNA content.…”
Section: Asf1 and Rfc Function Together To Promote S-phase Progressionmentioning
confidence: 68%
“…rfc1-1 cells have elongated telomeres (Adams and Holm 1996), suggesting poor coordination of telomeric C-rich strand synthesis by the lagging strand machinery and G-rich strand synthesis by telomerase in these cells (Diede and Gottschling 1999). To rule out the possibility that hyperelongated telomeres were the cause of the Sphase delay in asf1⌬ rfc1-1 cells, telomere lengths were assayed.…”
Section: Asf1 and Rfc Function Together To Promote S-phase Progressionmentioning
confidence: 99%
“…The original POL1 mutant described by Carson and Hartwell (1985) is a hypomorphic ts-lethal allele, presumably affecting the catalytic activity of the enzyme, that displays continual telomere elongation when grown at permissive or semipermissive temperatures, as well as elevated, RAD52-dependent recombination near telomeres. A more detailed examination of the pol1-1 telomere phenotype (Adams and Holm 1996;Adams Martin et al 2000) has revealed an S-phase-specific increase in singlestranded telomeric TG-repeat DNA, as well as a severe loss of telomeric silencing. Both of these phenotypes precede the telomere length increase seen after temperature up-shift, and are largely independent of telomerase action, suggesting that they are due to a primary defect in telomeric lagging-strand synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations in either protein that affect this interaction lead to a slight increase in average telomere length, but cause no other obvious phenotypes. However, mutations that affect the catalytic function of Pol1 and are lethal at elevated temperatures cause considerable and progressive telomere elongation, large increases in TG-specific single-stranded DNA at telomeres, and a loss of telomeric gene silencing (Carson and Hartwell 1985;Adams and Holm 1996;Adams Martin et al 2000). These and other data have led to the idea that Pol1, or the complete DNA polymerase ␣-primase complex, plays an important role in the down-regulation of telomerase action at telomeres, perhaps in a concerted regulatory step that ensures the replication of the CA-rich strand at chromosome ends.…”
mentioning
confidence: 99%